Liver enzymes activity in periparturient high and low yielding Sahiwal and Karan Fries Cows during summer and winter season - Vaidya, Mangesh M; Singh, Sohan Vir (Indian Journal of Dairy Science, 2019)
Ten each of pregnant Sahiwal and Karan Fries cows were selected from Livestock Research center, ICAR- NDRI, Karnal (Haryana) during summer and winter season separately. These animals were further divided equally (5 each) into two groups i.e. high and low producing. All the animals were maintained under existing feeding and management system followed at the farm. To quantify the effects of thermal and metabolic stress on liver enzymes (alkaline phosphatase and Lactate dehydrogenase), Â blood samples were collected from periparturient high and low producing Sahiwal and Karan Fries cows on days -45, -30, -15 (before calving), and 15, 30, and 45 (After calving) with respect to day of parturition (0) . The results showed that the alkaline phosphatase (ALP) activity in blood plasma of high and low yielding Sahiwal cows decreased by 5.6 and 7.6% and in Karan Fries the decline was 10.8 and 4.7% on the day of calving from the pre calving values (45 day) respectively during summer season. During winter season the ALP activity in blood plasma of high and low yielding Sahiwal cows decreased by 19.7 and 12.8% on 30th and 15th day of calving, where as in Â Karan Fries cows the activity decreased by13.9 and 9.75% on 15th day ofpostpartum and on the day of calving from the pre calving values (45 day) respectively. The magnitude of increase in Lactate dehydrogenase (LDH) activity was higher on 15th day postpartum compared to pre and post calving period in high and low yielding groups of both the breeds. The plasma activity of LDH in high and low yielding Sahiwal cows increased by 17.7 and 12.6% on the day of calving from the pre calving values (45day) respectively during summer season. During winter season the values of plasma LDH activity in high and low yielding Sahiwal cows increased by 43.7 and 48% respectively on the 15th day of calving from the pre calving values (45 day). The results showed significantly higher activity of both the enzymes (ALP and LDH) in Karan Fries cows, higher yielders and during summer compared to Sahiwal, low yielders and winter season respectively indicated that higher yielding cows (specially Karan Fries) showed be protected from heat stress for sustain milk production.